Development of the bus passenger origin-destination table of EDSA-Commonwealth routes - Neri, Angelica Dawn Q.; Sunga, Abigail P.; Vergel, Karl B. N. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
The daily bus passenger origin destination table is developed for the EDSA - Commonwealth bus routes. The OD survey data for seven routes gathered from the Mega Manila Public Transport Planning Support System published in 2012 are expanded using the results of a Bus Frequency Survey to acquire the daily OD table for each route which are later on combined into a single daily bus passenger OD table. Using the OD Table, the boarding and alighting and load profiles for each route have been constructed and used for the analysis of the supply of bus units and demand of bus passengers. Many of the bus units operating in EDSA and Commonwealth have very low occupancies even during morning and afternoon peak hours and are therefore oversupplied. The top ten origin - destination pair for the daily OD table developed is SLEX Metropolis - SLEX Sucat Exit. In addition, the top origins and destinations have also been selected for EDSA and Commonwealth. The top origin is Belfast-SM Annex while the top destination is SLEX-Bicutan Exit. The MMDA Bus Segregation Scheme is also found applicable to the routes being studied. Possible impacts of route modification have also been assessed, assuming that a proposal for an exclusive EDSA bus exists. Through further examination of the OD shares per route and for the daily OD table, only three out of the seven routes are retained to be operated along the entirety of the route while the rest are either the route being cut or the number of operating units reduced at certain segments.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Origin and destination traffic surveys; Bus stops -- Philippines -- Manila Metropolitan Area